The secret life of fat : the science behind the body's least understood organ and what it means for you - Tara, Sylvia (W.W. Norton & Company, 2017)
Blends historical perspectives with cutting-edge research to examine body fat as a critical endocrine organ that can be better understood and managed when recognized as a necessary component of human health.